The Conception of Cultural Space Revitalization as a Way to Increase Downtown Attractiveness. A Case Study of Chosen Medium-Sized Towns in the Wielkopolska Region - Pazder, Dominika (Quaestiones Geographicae, 2011)
This paper deals with chosen aspects of revitalization within the downtown area of Polish medium-sized towns. The author underlines the necessity of introducing a mixed-use offer in the city centre. Not only commerce and services, but also cultural functions and values should be promoted in the contemporary city centre. Therefore the idea is presented of turning the downtown public space into a single, homogeneous and integrated spatial-functional system. The system is to introduce cultural functions on the basis of so-called cultural space, which is defined here as a specific kind of public space of historical or cultural value, or that has the potential to develop this kind of new functions.